Open Graded Asphalt Mixtures in Chile - Rioja, Hector (2025)
The asphalt mixtures commonly used in road construction are of the dense or coarse type. For the sake of clarity, these mixtures will hereafter be referred to as conventional. In wearing courses, dense mixtures are generally used, while in intermediate or base layers, either dense or coarse mixtures are applied.